Comparison of booklet educational media effectiveness toward exclusive breastfeeding adherence - Nur Rahmawati Sholihah (Alma Ata University Press, 2023)
Background: Exclusive breastfeeding provides infants with breast milk and no additional food, water, or other liquids (except medicines and vitamins, if necessary) for the first 6 months of life. Current practice of exclusive breastfeeding in Indonesia among infants aged 4-5 months is 27%, while between age 5-6 months is 3.4%. The main contributing factors of the poor adherence to exclusive breastfeeding is the lack of knowledge, which affects behavior and motivation. Producing inclusive, appropriate, and acceptable media is essential to manage this issue.Objectives: The current study aimed to compare the effectiveness between application and booklet as educational media toward mother's adherence in exclusive breastfeeding.Methods: A quasi experimental study with pre-post test with control group design carried out. The research subjects were mothers with infants aged 4-6 months in the adminstrative area of the Gamping II Public Health Center, Sleman Regency and consist of 3 villages; Banyuraden (8 hamlet), Nogotirto (8 hamlet), Trihanggo (12 hamlet) Sample determined with purposive sampling, while recruitment performed by simple random sampling. The number of samples in the control and intervention grups were 32 respondents, and total sample is 64. Exclusive breastfeeding adherence was evaluated by knowledge, and attitudes questionnaire, validated with breastfeeding record within 24 hours. Comparative analysis was performed with Mann Whitney and Mc Nemar test.Results: p value yielded from pretest and posttest in the intervention group p=0.109. It was inferred that there was no significant difference of breastfeeding adherence in association with the intervention. The control group p value was p=0.039 indicating significant difference of adherence in breastfeeding practice.Conclusions: Booklet improves adherence to exclusive breastfeeding due to the depth of materials, familiar for the intended audience, practical, easy for content distribution, visually captive, attractive and easy to use. In-app educational media could increase knowledge and attitudes in particular to exclusive breastfeeding